2020
DOI: 10.1002/gcc.22924
|View full text |Cite
|
Sign up to set email alerts
|

A genome‐wide study of the relationship between chromosomal abnormalities and gene expression in colorectal tumors

Abstract: The role of somatic copy number alterations (SCNAs) that occur in colorectal tumors is poorly understood. SCNAs are correlated with corresponding gene expression changes that may contribute to neoplastic progression. Thus, we examined SCNAs and the expression of messenger RNAs (mRNAs) located at corresponding loci in colorectal neoplasia, a progression model of human neoplasm. We used 42 colorectal neoplastic samples, including adenomas, intramucosal cancers (IMC) and invasive colorectal cancers (CRC) that wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
2
19
0
Order By: Relevance
“…However, none of the genes corresponding to these gains showed altered expression. This finding suggests that although CN gains at 20q11.21–q13.33, 8q13.3, 8p23.1, or 8q21.2–q22.2 may be an epiphenomenon in the progression from adenoma to carcinoma, as suggested previously, 24 , 25 CN gain in the carcinomatous component may play a role in colorectal carcinogenesis. SCNAs may become candidate molecular markers predicting the risk of progression from adenoma to carcinoma.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…However, none of the genes corresponding to these gains showed altered expression. This finding suggests that although CN gains at 20q11.21–q13.33, 8q13.3, 8p23.1, or 8q21.2–q22.2 may be an epiphenomenon in the progression from adenoma to carcinoma, as suggested previously, 24 , 25 CN gain in the carcinomatous component may play a role in colorectal carcinogenesis. SCNAs may become candidate molecular markers predicting the risk of progression from adenoma to carcinoma.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, we found that a specific genotype defined by SCNAs with altered expression of the corresponding gene plays an important role in CRC progression 25 . In the present study, we showed that five genotypes involving CN gain with upregulated expression of the corresponding gene ( RPS21, MIR3654, RSP20, SNORD54 , and ASPH ) are closely associated with progression from the adenomatous to carcinomatous component of the same tumor.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Identification of target genes will require both genomic and functional studies ( 25 ). For focal events, the copy number profiles of higher resolution analysis can help narrow the list of candidates ( 26 ). However, we could not find correlations between the region displaying SCNAs at 2p14-16 with corresponding gene expression, which may suggest that genomic changes derived from cancer cells occur randomly during neoplastic progression, regardless of functional alterations in mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Human OLFM4, originally termed human cloned from myeloid precursor cells after granulocyte colony-stimulating factor stimulation, is a secreted glycoprotein more commonly known as the antiapoptotic molecule GW112 . More recently, upregulated OLFM4 expression has been described in lung and breast, prostatic, gastric, , and pancreatic , cancers and in colorectal adenomas, , and it has been suggested that OLFM4 is involved in cellular processes, such as apoptosis and tumor growth …”
Section: Discussionmentioning
confidence: 99%